PENGARUH PROFITABILITAS, PELUANG PERTUMBUHAN, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DIMEDIASI STRUKTUR MODAL - Berenice, Muliawati; Cahyadi, Hadi (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to analyze the effect of profitability, growth opportunities, and liquidity on company value in family companies in the property & real estate sector listed on the Indonesia Stock Exchange in 2019-2021. The selection of the sample in this research was carried out using a purposive sampling technique. The samples obtained in this study were 29 companies with a period of three years. Data processing techniques in this study used the SmartPLS 4.0.8.4 and Microsoft Excel programs. The results showed that profitability and liquidity do not significantly effect on capital structure, and growth opportunities had a positive and insignificant effect on capital structure. Profitability and capital structure have a positive and insignificant effect on firm value, growth opportunities and liquidity do not significantly effect the value of a company. Profitability has no significant effect on firm value mediated by capital structure, growth opportunities have an insignificant effect on firm value mediated by capital structure, and liquidity has a negative and insignificant effect on firm value mediated by capital structure.